Based on Outseal Studio and Haiwell Cloud Scada to Check Parking System Availability using Arduino Nano on The Miniature Parking Lot - Sulistiawan, Henri; Astutik, Rini Puji; Ristanto, Yunani (PROGRAM STUDI TEKNIK ELEKTRO, 2023)
In technological developments in the industrial era 4.0, especially in the field of electronics, the concentration of control is in the form of industrial automation systems. This development began with the emergence of several controllers, including microcontrollers and microprocessors. One of the functions of this development is to make human work easier by controlling a system automatically, for example automated parking. In this article, a method for designing and making a prototype of a Based on Outseal Studio and Haiwell Cloud Scada to Check Parking System Availability using Arduino Nano on The Miniature Parking Lot is written. The work process in this system is to monitor work flow in the area of a parking slot and record the number of vehicles in each slot. parking. This system is controlled via Arduino nano PLC which then displays using SCADA, namely Haiwell Could SCADA. This parking system is designed to connect parking slots, open automatic door latches and provide information in the form of data reports for each slot to the parking attendant. The results of implementing this system are able to make it easier for parking officers to control the parking area as well as increase the security of the parking area and minimize the loss of vehicles parked in each slot.Keyword: Arduino nano PLC,Outseal studio,SCADA,Slot,Parking area